Silyl Radical Activation of Alkyl Halides in Metallaphotoredox Catalysis: A Unique Pathway for Cross-Electrophile Coupling - Zhang, Patricia (J Am Chem Soc, 2016)
A strategy for cross-electrophile coupling has been developed via the merger of photoredox and transition metal catalysis. In this report, we demonstrate the use of commercially available tris(trimethylsilyl)silane with metallaphotoredox catalysis to efficiently couple alkyl bromides with aryl or heteroaryl bromides in excellent yields. We hypothesize that a photocatalytically generated silyl radical species can perform halogen-atom abstraction to activate alkyl halides as nucleophilic cross-coupling partners. This protocol allows the use of mild yet robust conditions to construct C(sp)(3)–C(sp)(2) bonds generically via a unique cross-coupling pathway.